Effectiveness of Sentence-By-Sentence Self-Monitoring (SSSM) A Strategy to Improve Reading Comprehension of Children with Nonverbal Learning Disability (NLD) - Chia, Noel Kok Hwee; Tee Ng, Angie Gek (Journal of the American Academy of Special Education Professionals, 2008)
Very little is known about Nonverbal Learning Disability (NLD) as the condition has no recognized, official diagnostic criteria. The awareness and support for children with NLD is far from desired levels, and no formal research studies have been done in Singapore. Hence, teaching children with NLD can be the most challenging to teachers here. The writers have chosen to work with these children with NLD in hope that with a better understanding of the NLD syndrome better intervention strategies can be developed especially in the area of reading comprehension. In this study, the writers selected the Sentence-by-Sentence Self-Monitoring (SSSM) method to teach reading comprehension to five children diagnosed with NLD to examine its effectiveness as an intervention strategy.